Analysis Convergence of Income Per Capita Among Regions in West Java 2017-2021 - Rizqa Nurhanifah Saputri (Universitas Negeri Semarang, 2024)
This research aims to identify the sigma and beta convergence of GRDP per capita, analyze the effect of Local Revenue (PAD), Human Development Index, working workforce, minimum wage, and industry on income per capita in West Java 2017-2021. The data used are secondary data from BPS. The analytical of sigma convergence uses coefficient of variation of GRDP per capita and panel data regression for beta convergence analysis with the best model being the Fixed Effect Model (FEM) Generalized Least Square (GLS) method. The results of this study indicate that there is a convergence of sigma GRDP per capita between districts / cities of West Java in 2017-2021, but general there is no absolute beta convergence or conditional beta. This means that income inequality between regions in West Java has decreased during 2017-2021, but developing regions have not been able to increase high economic growth compared to developed regions, resulting in divergence. The PAD and HDI have a positive effect on GRDP per capita. Minimum wage and industry have a negative effect. Meanwhile, the labor force that works has no effect on GRDP per capita.